Pedagogical Riskology: Preparing Future Teachers For Professional Activity In Conditions Of Uncertainty (Journal of Pedagogical Inventions and Practices, 2026)
The rapid transformation of contemporary society, driven by technological innovation, globalization, and socio-cultural change, has fundamentally altered the professional landscape of education. Teachers increasingly operate in conditions of uncertainty characterized by unpredictable classroom dynamics, diverse learners’ needs, educational reforms, and crises such as pandemics or social instability. Pedagogical riskology, as an emerging interdisciplinary field, examines the nature of risks in educational environments and proposes strategies for their management. This article explores the concept of pedagogical riskology and its role in preparing future teachers for professional activity under uncertain conditions. It discusses theoretical foundations, types of pedagogical risks, core competencies required for risk-informed teaching, and methodological approaches to integrating riskology into teacher education programs